Banking Services for Everyone? Barriers to Bank Access and Use around the World - Beck, Thorsten (World Bank, 2012)
Information from 209 banks in 62 countries is used to develop new indicators of barriers to banking services around the world, show their correlation with measures of outreach, and explore their association with bank and country characteristics suggested by theory as potential determinants. Barriers such as minimum account and loan balances, account fees, and required documents are associated with lower levels of banking outreach. While country characteristics linked with financial depth, such as the effectiveness of creditor rights, contract enforcement mechanisms, and credit information systems, are weakly correlated with barriers, strong associations are found between barriers and measures of restrictions on bank activities and entry, bank disclosure practices and media freedom, and development of physical infrastructure. In particular, barriers are higher in countries where there are more stringent restrictions on bank activities and entry, less disclosure and media freedom, and poorly developed physical infrastructure. Also, barriers for bank customers are higher where banking systems are predominantly government-owned and are lower where there is more foreign bank participation. Larger banks seem to impose lower barriers on customers, perhaps because they are better positioned to exploit economies of scale and scope.